To treat or not to treat: Experiences and considerations of veterinarians in management of cats with diabetes mellitus - Ninni Rothlin-Zachrisson; Bodil Ström Holst; Malin Öhlund; Janeth Leksell; Helena Röcklinsberg (PLoS ONE, 2026)
Veterinarians’ daily work involves navigating ethical, medical, and emotional considerations while balancing diverse perceptions of responsible care within the triadic relationship between veterinarian, animal, and owner. These challenges are particularly evident in the management of chronic diseases. Diabetes mellitus serves as an example in our study, where we explore Swedish veterinarians’ experiences of managing it in cats. Individual in-depth interviews were conducted with ten veterinarians, and the data were systematically analysed using reflexive thematic analysis. One overarching theme, the perceived prioritisation of the cat’s wellbeing, was identified as central to how veterinarians approached the clinical situation. Three themes are addressed: the role of the owner in disease management, the negotiation between medical ideals and practical realities, and the perception of euthanasia as being in the best interest of the cat. Taken together, the three themes explore how veterinarians continually negotiate what it means to act responsibly within the constraints of real-life practice. This ongoing negotiation between ideals, pragmatism, and compassion underscores the ethical depth and emotional labour embedded in everyday veterinary work. The results contribute in-depth insights into how clinical reasoning and decision-making is shaped by both moral positions and pragmatic adaptations, and the importance of veterinary-owner communication in finding the optimal management plan in each individual case. Awareness of the challenges associated with diabetes care in cats may facilitate ethical reflexivity in veterinary practice, supporting decisions that impact both animal welfare and veterinarians’ professional wellbeing.